A comparison of writing tasks in ESL writing and first-year composition courses: A case study of one US university. (May 2021) - Lee, Jooyoung
Many international students in American universities are required to take writing courses in English as a second language (ESL) before participating in a mainstream first-year composition (FYC) course. Given that the goal of ESL writing course is to prepare students for FYC course, the connection between ESL and FYC courses is significant. This study investigates the correspondence of two such courses in terms of writing tasks based on the analysis of course syllabi, assignment sheets, and interviews with eight ESL course and 10 FYC instructors as well as 26 international students who are from diverse countries and took both composition courses. The findings suggest that students' assignments from both courses are all essays in terms of genre, but show differences with regard to the text's purpose, audience, information source, topic, and rhetorical function. Students are also aware of such similarities and differences, but occasionally demonstrate less sophisticated or inaccurate understanding of the assignments. Pedagogical implications for modifying the writing assignments in ESL courses to fit the expectations of FYC courses are discussed.